Aerodynamic analysis of wind turbine blades: A numerical study - İlker Yılmaz; Ayşegül Avci; Ekin Aköz Arslankaya (Gazi Üniversitesi Fen Bilimleri Dergisi)
In this study, the aerodynamic performance of different wind turbine blades including FX 63-137, NACA 6415, NACA 63-415 has been investigated. XFLR5 has been employed to analyze the wind turbine blade at Reynolds numbers ranging from 1.5x105 to 1x106 and low angles of attack (00≤α≤200). The lift (CL), drag(CD), and pitch moment (CM) coefficients, and lift/drag coefficient ratio (CL/CD) of the wind turbine blades have been evaluated. Numerical lift coefficients obtained using XFLR5 and lift coefficients from the literature have beeen compared and it has been found that they have been compatible with each other. According to numerical analyzes, the highest lift coefficient-to-drag coefficient ratio, as called aerodynamic efficiency, was obtained as 109.14 with FX63-137 blade at Re number of 1x106, the lowest lift coefficient-to-drag coefficient ratio was obtained as 2.63 with NACA 63-415 blade. Also, the maximum lift coefficient-to-drag coefficient ratio with the NACA 63-415 blade profile was 104.28, while that for the NACA6415 blade profile was 102.11 at Re number of 1x106. The analysis results show that lift coefficient-to-drag coefficient increases with the increase in the angle of attack up to the stall angle, and then begins to decrease in all studied blades.